Allelopathic effect of multipurpose woody perennials on understory crops of Mizoram, North-East India - Lalnunhluva, L.; Upadhyaya, K.; Sahoo, U.K. (Indian Journal of Agroforestry, 2019)
Laboratory bioassay and pot culture experiments were conducted to assess the effect of three important multipurpose woody perennials, namely Parkia timoriana, Acacia pennata and Trevesia palmata on germination, radicle and plumule extension and growth of four important understory crops, namely Zea mays, Cajanus cajan, Abelmoschus esculentus and Solanum anguivi commonly occurring in agroforestry systems of Mizoram, North-East India. All the woody perennials exhibited inhibitory effects on germination of the test crops in bioassay experiment. The tested woody perennials significantly reduced germination of S. anguivi (ranged between 47.5–52.5%) when compared with control (80%). A. pennata and T. palmata had significant inhibitory effect on germination of C. cajan (60% compared to 73.3% in control) and A. esculentus (52.5–57.5% as compared to 80% in control). T. palmata showed the highest phytotoxic effect with 7-28% reduction in shoot growth and 34-56% decrease in dry matter production in comparison to control while Z. mays was least affected among tested crops. P. timoriana had least effect on studied test crops and therefore, can comfortably be grown under agroforestry systems.